Editorial: The Role of the Social Economy in Supporting, Challenging and Innovating Canadian Social Policy - Sousa, Jorge; Wulff, Stuart (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2012)
This is the editorial so there is no abstract